Dissolved oxygen and inorganic carbon dynamics in a high-energy coastal environment near Victoria BC’s untreated municipal sewage outfalls - Krogh, Jeremy (2017)
Wastewater disposal often has deleterious impacts on the receiving environment. Low levels of dissolved oxygen are of particular concern. Here I investigate the impacts on dissolved oxygen and carbon chemistry of screened municipal wastewater in the marine waters off Victoria, B.C., Canada. I analyzed data from a series of undersea moorings, ship-based monitoring, and underwater remotely-operated vehicle video. I used these observations to construct a two-layer box model of the nearfield receiving environment. Despite the lack of more advanced treatment, dissolved oxygen levels near the outfalls are well above the commonly used 63 umol kg-1 hypoxic threshold and that the outfalls’ impact on water column oxygen is likely less than a few umol kg-1. Likewise, dissolved inorganic carbon is not elevated and pH not depressed compared to the surrounding region. Strong tidal currents and the cold, well-oxygenated waters of Victoria’s marine environment give these waters a high assimilative capacity for organic waste. Graduate 0595 0403 0543 jeremykrogh@gmail.com